Politicization of science in the Lancang–Mekong Basin: the Eyes on Earth Study. Issue 2 (4th March 2023) - Grünwald, Richard; Feng, Yan; Wang, Wenling
ABSTRACT: In April 2020, the Eyes on Earth published a comprehensive research study presenting new evidence about the changing dynamics of the Lancang–Mekong River water flow. The Eyes on Earth Study (EoE Study) received significant media attention and raised concerns about hydrological changes that negatively affect the downstream countries. By drawing on the politicization of science theories and using the Lancang–Mekong Cooperation and Conflict Database, we (1) provide an overview the EoE Study's findings; (2) outline the scientific and non-scientific responses to the EoE Study's conclusions; and (3) study various implications of the politicization of the EoE Study.